2018
DOI: 10.1007/s10142-018-0607-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection

Abstract: Rhizoctonia solani causes rice sheath blight, an important disease affecting the growth of rice (Oryza sativa L.). Attempts to control the disease have met with little success. Based on transcriptional profiling, we previously identified more than 11,947 common differentially expressed genes (TPM > 10) between the rice genotypes TeQing and Lemont. In the current study, we extended these findings by focusing on an analysis of gene co-expression in response to R. solani AG1 IA and identified gene modules within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…RNA sequencing (RNA-seq) analysis is a critical, easy, rapid, and economical approach of transcriptome studies [37]. Different stress responsive genes have been identified by RNA-seq analysis and their expression under salinity stress already been clarified in various plants including Glycine max [38], rice [39], sweet potato [40], and wild barley [41]. RNA-seq generates a bundle of information for a target phenotype or stress; however, resourceful utilization of this data has been a bottleneck.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) analysis is a critical, easy, rapid, and economical approach of transcriptome studies [37]. Different stress responsive genes have been identified by RNA-seq analysis and their expression under salinity stress already been clarified in various plants including Glycine max [38], rice [39], sweet potato [40], and wild barley [41]. RNA-seq generates a bundle of information for a target phenotype or stress; however, resourceful utilization of this data has been a bottleneck.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factors including NAC, WRKY, and basic leucine zipper (bZIP) family members differentially regulate the expression of various defense genes and are involved in modulating resistance to R. solani (Olsen et al 2005 ; Zhang et al 2018 ). NAC transcription factors are involved in the regulation of signal transduction pathways mediated by salicylic acid (SA), JA, ethylene and abscisic acid (Zhao et al 2020 ).…”
Section: Countermeasures From the Hostmentioning
confidence: 99%
“…These results provided new information of the pathogenic process. Zhang et al [17,18] compared the transcriptome changes of leaves between TeQing (a moderately resistant cultivar) and Lemont (a susceptible cultivar) cultivars in response to R. solani infection. The results showed that regulation of photosynthesis, photorespiration, jasmonic acid and phenylpropanoid pathways might contribute to rice resistance to R. solani.…”
Section: Introductionmentioning
confidence: 99%